Efeito de Terminalia catappa L. em leveduras de Candida: avaliação in silico, in vitro e in vivo - SANTOS, Giselle Cutrim de Oliveira (2018)
Terminalia catappa Linn is a plant typical of tropical regions, which presents some biological activities already described, among them the antifungal, observed in Candida. In spite of this report, this work sought to extend the investigation of this activity to other fungal strains, as well as a better characterization of this activity and the possible chemical components of the T. catappa Hydroethanolic Extract (EB). It was also sought, through computational simulations, to predict the in silico activity of T. catappa compounds and to investigate the use of this plant species in the in vivo treatment of mice in candidemia models. After preparation of EB, the phytochemical analysis and chemical characterization of the extract were performed by HPLC-UV, LC-ESI-IT-MS and FIA-ESI-IT-MSn. In the attempt to separate the constituents of T. catappa, EB was subfracted by classical column chromatography with silica gel, and those compounds with polarity similarity were evaluated at the CCD and assembled. For in silico analysis, the compounds identified by LC-ESI-IT-MS in EB were structurally schematized in 3D. The CaCYP51 structure of C. albicans and ligands was prepared for the molecular docu- mentation calculations and, afterwards, the simulations were carried out by molecular dynamics. Cell viability of EB and aqueous (FAq) and dichloromethane fractions (FDCM) was determined by the MTT method. To evaluate the antifungal action of EB, agar diffusion and microdilution tests were performed with Candida strains. In the evaluation of the survival of mice, a model of immunosuppression with cyclophosphamide 50 mg / kg 48h before the beginning of the infection with C. albicans (3x108) was used. Treatments with amphotericin B (0.6 mg / kg), EB (10 mg / kg) and EB (100 mg / kg) were done 6 hours before infection or treated 6 hours after infection. The phytochemical analysis of EB revealed the presence of tannins, catechins, saponins, anthocyanins and anthocyanins, flavones, flavanols and xanthones, steroids and triterpenes in the extract. The chemical characterization of EB identified the compounds punicalagina, punicalina, galágico acid and elágico acid. From the subfractionation of 2 g EB, 570 subfractions were obtained and those with similar chromatographic profile were collected in 16 groups. In silico analysis, ellagic acid was the compound that presented the best affinity parameters in molecular docu- mentation calculations with CaCYP51. In cell viability, the IC 50 was 237.2; 148.0 and 206.2 μg / mL, respectively, for EB, FAq and FDCM. EB inhibited the formation of halos at concentrations of 25, 50 and 100 mg / mL and inhibited the growth of Candida in the microdilution assay at concentrations ranging from 0.007 to 4 mg / mL. The EB 10 group had a 40% survival and an increase in life expectancy of 54.5%. In conclusion, in the in silico model, the galágic acid presented affinity with the CaCYP51 of C. albicans, EB presented activity in vitro antifungal assays at the tested concentrations and increased the survival of immunosuppressed mice and with candidemia.